THE ESTIMATION OF GROWTH CURVE OF BALI CATTLE AT BONE AND BARRU DISTRICTS, SOUTH SULAWESI, INDONESIA USING TEN BODY MEASUREMENTS - Sri Rachma, A.B.; Harada, H.; Ishida, T. (Diponegoro University, 2011)
The estimation of growth curves and mature size of ten body measurements, namely withers height,hip height, body length, chest girth, chest depth, chest width, rump length, hip width, thurl width, andpin bone width, were studied in Bali bulls and heifers at the age of 12, 15, 18, 21 and 24 months. 108bulls and 146 heifers at Bone district and 152 bulls and 110 heifers at Barru district, South Sulawesi,Indonesia were measured. The Brody growth function was fitted to each animal’s records and leastsquaresanalysis were used to investigate the effects of place, sex, and age to growth curve and maturesize of body measurements of Bali bulls and heifers. The result showed that the growth of bodymeasurements of Bali cattle until 24 months of age were still increasing and not reaching the mature sizeyet. The place, sex and age factors were significantly affected to the growth of body measurements ofBali cattle.